An algorithm of wavelet data compression based on wireless sensor network - Luo, X. (Journal of Digital Information Management, 2013)
Firstly, this paper gives a data aggregation algorithm based on learning automata to solve the problem that the existing data aggregation algorithm can't solve, the uneven energy cost, and the existing algorithm can't change the gathering path dynamically existing the overhead environment. In the proposed method, nodes can change its gathering path to adjust the overhead environment. All the nodes of WSN equipped with a learning automata. These leaning automata learn all the gathering path of the nodes. In the process of transmit information two kinds of data are transmitted, including data packet, knowledge packet .When the information of the nodes changes, according to the feedback of the nods, the learning automata gives the reward or punish to the current gathering path, which help to find the best gathering path. Secondly, this paper improved the wavelet data compression algorithm, which was brought out as the correlation between different data. The algorithm do not reduce much of the data relate to the original data. After the wavelet data compression, Huffman coding compression algorithm will improve the data compression ratio.
Keywords: Data compression; Gatherting path; Hot node; Learning automata; Wavelet Transform

Dual watermarking scheme for copyright protection and authentication - Bhatnagar, G.; Raman, B.; Swaminathan, K. (Journal of Digital Information Management, 2009)
Digital Watermarking is used for copyright protection and authentication of digital media-image/audio/video data. In this paper, a novel dual watermarking scheme is described based on Discrete Wavelet Transforms (DWT) and Singular Value Decompositions (SVD). Unlike the existing dual watermarking schemes, both the watermark embedded using DWT and SVD are invisible in the proposed scheme. For embedding, both the images are transformed into Wavelet domain and SVD is performed further on both the images. Subsequently the singular values are summed up to find the new set of singular values. Both the watermarks get embedded in the same manner. A reliable watermark extraction scheme has been developed for the extraction of the watermarks from the distorted image. Experimental evaluation demonstrates that the proposed scheme is capable of withstanding variety of attacks.
Keywords: Digital dual watermarking; Gray-scale logo; Multiresolution analysis; Singular Value Decomposition; Wavelet Transform; Zig-zag sequence